Lex Injusta Non-Est Lex: Article 74 Trademark Law versus Constitutional Economic Democracy in Indonesia’s SME Protection - Ricky Thio; Siti Nur Azizah; Wagiman; Dyah Ersita Yustanti (Research Horizon, 2025)
This research examines the structural contradiction between Article 74’s three-year trademark non-use cancellation provision in Law Number 20/2016 and the People-Based Economy principle of Article 33, 1945 Constitution. This capitalistic norm facilitated predatory litigation against vulnerable MSMEs, constituting philosophical lex injusta. Using normative juridical methodology with case and comparative law approaches, this study justifies arguments from the successful Constitutional Court petition. Constitutional Court Decision Number 144/PUU-XXI/2023 provides the judicial solution by extending non-use period to five years, resolving unconstitutionality. The study distinguishes Article 74’s objective non-use standard from Article 76’s subjective bad-faith element, establishing the former now prescribes constitutionally equitable timeframe. The five-year period aligns with SME business cycles for research, development, and market penetration, providing protection from premature cancellation threats. This judicial reform represents substantive constitutional justice, granting MSMEs legal certainty for intellectual asset development. The victory harmonizes Indonesia’s trademark law with People-Based Economy commitments. Primary recommendations include developing accessible evidentiary guidelines for trademark use documentation, particularly digital-based systems, and creating affordable platforms for SMEs to systematically document commercial activities, ensuring effective intellectual property defense within this equitable legal landscape.